-12n-12=-11n

Simple and best practice solution for -12n-12=-11n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12n-12=-11n equation:


Simplifying
-12n + -12 = -11n

Reorder the terms:
-12 + -12n = -11n

Solving
-12 + -12n = -11n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '11n' to each side of the equation.
-12 + -12n + 11n = -11n + 11n

Combine like terms: -12n + 11n = -1n
-12 + -1n = -11n + 11n

Combine like terms: -11n + 11n = 0
-12 + -1n = 0

Add '12' to each side of the equation.
-12 + 12 + -1n = 0 + 12

Combine like terms: -12 + 12 = 0
0 + -1n = 0 + 12
-1n = 0 + 12

Combine like terms: 0 + 12 = 12
-1n = 12

Divide each side by '-1'.
n = -12

Simplifying
n = -12

See similar equations:

| (-4v+3)(8v+6)=0 | | 9400=10 | | 9y-4y-14=48.80 | | 8.2x-53.4=-24.6 | | (t)=4t+3t^3+2t-7 | | -28-3n=8+6n | | X/5=33 | | 4v-13=59 | | 7b+8=4b-10 | | 4x+24=17 | | 54c+45d= | | 0=1-3sin(3x) | | 53=28-5(x-1) | | p-2.50=4a+10 | | X+45=77 | | 9x+3-3=0 | | 3x*-5x+2=0 | | 0.1x+.7=3.5 | | 21345/15 | | 4+8(1-9b)=-34 | | X-84=123 | | 0.9=0.3b | | 0.3(3z+7)+4.5=0.4(3z-6) | | 0.4x=2.6 | | 108+6x=270 | | 12-9+m+3-5=-10 | | 5m+8=2-9m | | 2*cosx*tanx-tanx=0 | | 21345=n/15 | | 10=48t-16t^2 | | 10=12x+32 | | 3(.5y)-6y=9 |

Equations solver categories